PENGARUH PDRB, JUMLAH PENDUDUK, IPM, DAN PANDEMI COVID-19 TERHADAP PENGANGGURAN DI PROVINSI BALI - Perilia, Ni Komang Ayu; Mustika, Made Dwi Setyadhi (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 12 No 9 (2023): Vol.12.No.9.SEPTEMBER. 2023[586-649]DO - 10.24843/EEP.2023.v12.i09.p05, 2023)
The problem that most often arises in development is unemployment. Development will be hampered if unemployment increases because it triggers the emergence of new problems in the economic and social fields. According to Sukirno (2006), unemployment is a situation where a person included in the labor force wants to get a job but has not got it yet. The purpose of this study was to determine the effect of the Gross Regional Domestic Product (GDP), Total Population, Human Development Index (IPM), and the Covid-19 Pandemic on the unemployment rate in the Province of Bali. The data used is secondary data, namely unemployment data, Gross Regional Domestic Product (GDP), Population Projection, Human Development Index (IPM), and the Covid-19 Pandemic as a dummy variable. This research was conducted in 8 regencies and 1 city in Bali Province from 2017-2021. This study was tested using panel data regression analysis techniques with the selected estimation model, namely the common effect model using Eviews software. The results of the research conducted show that the Gross Regional Domestic Product (GDP) has a negative and significant effect on unemployment, total population has no significant effect on unemployment, the Human Development Index (IPM) and the Covid-19 Pandemic have a positive and significant effect on unemployment in the Province of Bali. keyword : Unemployment, GRDP, Total Population, HDI, and the Covid-19 Pandemic.